Product Attribute Innovation of Capcin Creamy and Spicy Basreng in Generation Z Market Segmentation: INOVASI ATRIBUT PRODUK CAPCIN CREAMY DAN BASRENG PEDAS PADA SEGMENTASI PASAR GENERASI Z - Maulana, Akbar; Tata, Ika; Ayu, Febri; Alvina, Nadia; Fitroh, Vito; Yuliastuti, Rika (Green Engineering Society, 2026)
ABSTRACT. The goal of this research is to determine how product attribute improvements in Basreng Pedas and Capcin Creamy affect Generation Z's purchase interest, the main consumer market being targeted. The study used a descriptive qualitative method, using field observations of offline sales during the Car Free Day (CFD) event in Taman Bungkul and online sales from WhatsApp, Instagram, and TikTok. The information was gathered through sales data, field notes, and visual documentation. According to the findings, the main variables influencing Generation Z's tastes and purchasing decisions are flavor innovation, aesthetics, and package design. Due to its spicy flavor and crunchy texture, which are consistent with the tastes of young people, Basreng Pedas had the highest purchase frequency, according to offline observations. On the other hand, internet sales data indicate that Capcin Creamy was ordered more often due to its appealing look and ability to be shared on social media. Additionally, price bundling tactics were shown to increase buying interest by providing increased perceived value. These results demonstrate that small firms in the contemporary culinary market can greatly improve their product attractiveness by using a combination of sensory innovation, visual presentation, and pricing strategies. ABSTRAK. Penelitian ini dilakukan untuk memahami bagaimana inovasi dalam atribut produk Capcin Creamy dan Basreng Pedas mempengaruhi keputusan beli generasi Z, yang merupakan kelompok konsumen utama. Metode yang diterapkan adalah deskriptif kualitatif dengan observasi lapangan, mencakup penjualan secara offline di Car Free Day (CFD) Taman Bungkul dan penjualan online dari WhatsApp, Instagram, serta TikTok. Data dikumpulkan dengan cara dokumentasi visual, catatan lapangan, dan ringkasan penjualan. Hasil studi menunjukkan bahwa inovasi rasa, desain tampilan, dan kemasan adalah elemen kunci yang memengaruhi preferensi dan minat beli gen z. Hasil dari observasi offline mengungkapkan bahwa Basreng Pedas menjadi produk dengan angka pembelian tertinggi, berkat sensasi pedas dan kerenyahan yang disukai oleh anak muda. Di sisi lain, penjualan online menunjukkan bahwa Capcin Creamy lebih diminati karena penampilannya yang estetis dan menarik di platform media sosial. Selain itu, strategi bundling harga terbukti efektif dalam meningkatkan minat beli dengan memberikan persepsi nilai yang lebih baik. Temuan ini menunjukkan bahwa perpaduan inovasi dalam aspek sensorik, visual, dan harga memiliki makna penting bagi UMKM dalam menarik perhatian konsumen di pasar kuliner modern.